Tests and Analyses of Slotted-In Steel-Plate Connections in Composite Timber Shear Wall Panels - Ulf Arne Girhammar; Bo Källsner (Advances in Civil Engineering)
The authors present an experimental and analytical study of slotted-in connections for joining walls in the Masonite flexible building (MFB) system. These connections are used for splicing wall elements and for tying down uplifting forces and resisting horizontal shear forces in stabilizing walls. The connection plates are inserted in a perimeter slot in the PlyBoard™ panel (a composite laminated wood panel) and fixed mechanically with screw fasteners. The load-bearing capacity of the slotted-in connection is determined experimentally and derived analytically for different failure modes. The test results show ductile postpeak load-slip characteristics, indicating that a plastic design method can be applied to calculate the horizontal load-bearing capacity of this type of shear walls.